Why Do the EU and Singapore Protect E-Commerce Consumers Better Than Indonesia? - Elva Elva; Hari Sutra Disemadi; Nurlaily Nurlaily; Mimi Sintia Mohd Bajury (Jurnal Kajian Pembaruan Hukum, 2025)
This study addresses the pressing research problem of how Indonesia’s existing legal enforcement framework fails to protect consumers from irresponsible e-commerce practices, in contrast with more advanced jurisdictions such as Singapore and the European Union. The primary objective of the research is to examine and compare the enforcement models employed in Indonesia, Singapore, and the EU, with a view to identifying strengths and gaps that may inform reforms in Indonesia’s legal system. Using normative legal research, employing both comparative legal and statutory approaches, the study relies on secondary legal materials and regulations from all three jurisdictions, and analyses them through descriptive qualitative methods underpinned by Progressive Legal Theory. The findings show the EU's leadership in data protection enforcement through strong turnover-based sanctions, independent supervisory bodies, cross-border dispute resolution, and rigorous due diligence. Singapore demonstrates moderate effectiveness through accessible consumer forums, robust PDPC enforcement, and compliance tools such as CaseTrust, though its scope remains limited. Indonesia lags behind, hindered by weak sanctions, fragmented oversight, underdeveloped dispute resolution mechanisms, and a lack of independent enforcement. These insights underscore the need for Indonesia to adopt systemic reforms, including turnover-based penalties, an independent data authority, integrated online dispute resolution, and coordinated regulatory frameworks, shifting from formalistic rules toward a progressive legal ecosystem that upholds consumer protection, accountability, and digital trust.